Altered Repolarization Reserve in Failing Rabbit Ventricular Myocytes: Calcium and β-Adrenergic Effects on Delayed- and Inward-Rectifier Potassium Currents. (February 2018) - Hegyi, Bence; Bossuyt, Julie; Ginsburg, Kenneth S.; Mendoza, Lynette M.; Talken, Linda; Ferrier, William T.; Pogwizd, Steven M.; Izu, Leighton T.; Chen-Izu, Ye; Bers, Donald M.
Abstract : Background: Electrophysiological remodeling and increased susceptibility for cardiac arrhythmias are hallmarks of heart failure (HF). Ventricular action potential duration (APD) is typically prolonged in HF, with reduced repolarization reserve. However, underlying K + current changes are often measured in nonphysiological conditions (voltage clamp, low pacing rates, cytosolic Ca 2+ buffers). Methods and Results: We measured the major K + currents ( I Kr, I Ks, and I K1 ) and their Ca 2+ - and β-adrenergic dependence in rabbit ventricular myocytes in chronic pressure/volume overload–induced HF (versus age-matched controls). APD was significantly prolonged only at lower pacing rates (0.2–1 Hz) in HF under physiological ionic conditions and temperature. However, when cytosolic Ca 2+ was buffered, APD prolongation in HF was also significant at higher pacing rates. Beat-to-beat variability of APD was also significantly increased in HF. Both I Kr and I Ks were significantly upregulated in HF under action potential clamp, but only when cytosolic Ca 2+ was not buffered. CaMKII (Ca 2+ /calmodulin-dependent protein kinase II) inhibition abolished I Ks upregulation in HF, but it did not affect I Kr . I Ks response to β-adrenergic stimulation was also significantly diminished in HF. I K1 was also decreased in HF regardless of Ca 2+ buffering, CaMKII inhibition, or β-adrenergic stimulation. Conclusions: At baseline Ca 2+ -dependent upregulation of I Kr and I Ks in HF counterbalances the reduced I K1, maintaining repolarization reserve (especially at higher heart rates) in physiological conditions, unlike conditions of strong cytosolic Ca 2+ buffering. However, under β-adrenergic stimulation, reduced I Ks responsiveness severely limits integrated repolarizing K + current and repolarization reserve in HF. This would increase arrhythmia propensity in HF, especially during adrenergic stress.